Health Status and Social Networks as Predictors of Resilience in Older Adults Residing in Rural and Remote Environments - Christine McKibbin; Aaron Lee; Bernard A. Steinman; Catherine Carrico; Katelynn Bourassa; Andrea Slosser (Journal of Aging Research)
Purpose. Health status and social networks are associated with resilience among older adults. Each of these factors may be important to the ability of adults to remain in rural and remote communities as they age. We examined the association of health status and social networks and resilience among older adults dwelling in a rural and remote county in the Western United States. Methods. We selected a random sample of 198 registered voters aged 65 years or older from a frontier Wyoming county. Hierarchical linear regression was used to examine the association of health status as well as social networks and resilience. We also examined health status as a moderator of the relationship between social networks and resilience. Results. Family networks (p=0.024) and mental health status (p<0.001) significantly predicted resilience. Mental health status moderated the relationship of family (p=0.004) and friend (p=0.021) networks with resilience. Smaller family and friend networks were associated with greater resilience when mental health status was low, but not when it was high. Conclusion. Efforts to increase mental health status may improve resilience among older adults in rural environments, particularly for those with smaller family and friends networks.